2021
DOI: 10.2196/26948
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Prevention Among College Students Before and During the COVID-19 Pandemic: Protocol for a Systematic Review and Meta-analysis

Abstract: Background Suicide is the second leading cause of death for college-aged individuals worldwide and in the United States. Recent studies have identified preliminary evidence of widening disparities in suicidal behaviors across sex, sexual orientation, race/ethnicity, age, and socioeconomic status among college students. Few systematic reviews and meta-analyses offer a comprehensive understanding of on-campus and off-campus suicide interventions, nor is collated information available for different ty… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…However, previous research has also demonstrated increases in suicidality for university student samples before the pandemic. The documented endorsement rate of 20% for suicidal ideation among university students, coincides with published increases in suicidal ideation within student populations over the previous decade, from 5.8% in 2007 to 10.8% in 2017 ( Mental Health - Household Pulse Survey - COVID-19 , 2022 ; Xiao et al., 2021 ).…”
Section: Discussionsupporting
confidence: 76%
“…However, previous research has also demonstrated increases in suicidality for university student samples before the pandemic. The documented endorsement rate of 20% for suicidal ideation among university students, coincides with published increases in suicidal ideation within student populations over the previous decade, from 5.8% in 2007 to 10.8% in 2017 ( Mental Health - Household Pulse Survey - COVID-19 , 2022 ; Xiao et al., 2021 ).…”
Section: Discussionsupporting
confidence: 76%
“…Existing suicide prevention efforts are dominated by risk reduction strategies 4 , 5 . However, meta-analyses have found that common risk factors, including sociodemographic characteristics, psychological factors, physical health, and social relationships, yield limited predictive power for fatal and nonfatal suicidal behavior 6 , 7 . Besides, suicide risk factors are typically identified through association studies and do not fully account for potential confounding 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Suicide among college students is a major public health problem ( 1 , 2 ), which can take a huge toll on society and cause untold psychological pain to their relatives ( 3 , 4 ). Individuals with suicidal ideation are more likely to make a suicide attempt ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%